Corporate Social Responsibility Sebagai Pemoderasi: Determinan Efisiensi Investasi - Devi, Ni Luh Ayu Asih Tirta; Darmawan, Nyoman Ari Surya; Atmadja, Anantawikrama Tungga (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to analyze the effect of ownership structure, financial reporting quality, and corporate governance on investment efficiency, and to test the role of Corporate Social Responsibility (CSR) as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2022 period. The results of the study indicate that ownership structure and financial reporting quality do not have a significant effect on investment efficiency. This condition is thought to be influenced by concentrated ownership, weak monitoring mechanisms, and low reliability of accounting information due to information asymmetry and financial reporting manipulation. In contrast, corporate governance has a positive and significant effect on investment efficiency, indicating the importance of effective managerial supervision. CSR is unable to moderate the relationship between ownership structure and financial reporting quality with investment efficiency, because its implementation is still symbolic and not strategic. However, CSR is able to moderate the relationship between governance and investment efficiency, indicating its role as a governance strengthening tool that encourages transparency, accountability, and more efficient investment decision making. This study presents novelty by showing that CSR is only effective as a moderator in the relationship between governance and investment efficiency, but not in ownership structure and financial reporting quality. The implication is that CSR needs to be integrated strategically to truly strengthen corporate governance and investment efficiency.